2012
DOI: 10.1063/1.4764929
|View full text |Cite
|
Sign up to set email alerts
|

Transport properties of silver selenomolybdate glassy ionic conductors

Abstract: Transport properties of silver selenomolybdate glassy ionic conductors have been reported for wide composition and temperature ranges. It has been observed that the transport properties of these glasses depend strongly on the modifier content as well as on the glass formers ratio. A direct correlation between the ion transport and the modification of the glass structure has been predicted. Transport properties of these glasses are also strongly influenced by the existence of dual character of SeO 2 as a glass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…A minimum in the conductivity is observed for y = 0.5. It has been observed that in undoped 0.3Ag 2 O-0.7(ySeO 2 -(1 À y) MoO 3 ) glasses the conductivity increases with the increase of the SeO 2 content up to y = 0.7 and then the conductivity decreases slightly for y = 0.8 20. From Fig.2(a) and (b) it is clearly seen that the value of the ionic conductivity is less affected by the network structure and is mainly influenced by the AgI content, i.e., the mixed network former effect in these glasses is overridden by the silver ion conductivity of AgI.…”
mentioning
confidence: 99%
“…A minimum in the conductivity is observed for y = 0.5. It has been observed that in undoped 0.3Ag 2 O-0.7(ySeO 2 -(1 À y) MoO 3 ) glasses the conductivity increases with the increase of the SeO 2 content up to y = 0.7 and then the conductivity decreases slightly for y = 0.8 20. From Fig.2(a) and (b) it is clearly seen that the value of the ionic conductivity is less affected by the network structure and is mainly influenced by the AgI content, i.e., the mixed network former effect in these glasses is overridden by the silver ion conductivity of AgI.…”
mentioning
confidence: 99%
“…However, for higher mixed former ratio, the SeO 3 2− ions have a tendency to bond with Ag + ions and form isolated Ag 2 SeO 3 crystalline structure, which in turn reduces the availability of the effective nonbridging hopping site. 16 It has been observed in various selenium− borate 38 and selenium−molybdate 16 glasses that, when sufficient Ag + ions are present in the glass structure, a part of SeO 2 participates in the formation of silver−selenite immobile structure. In a few selenite glasses containing Cu 2+ ions, the formation of a composite copper−selenite structure has been observed.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Initially, the vibration of SeO 3 2– ions is predominant, as the polarizability as well as the availability of the number of nonbridging hopping sites facilitates faster ion conduction. However, for higher mixed former ratio, the SeO 3 2– ions have a tendency to bond with Ag + ions and form isolated Ag 2 SeO 3 crystalline structure, which in turn reduces the availability of the effective nonbridging hopping site . It has been observed in various selenium–borate and selenium–molybdate glasses that, when sufficient Ag + ions are present in the glass structure, a part of SeO 2 participates in the formation of silver–selenite immobile structure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations